Penerapan Model Waterfall pada Sistem Manajemen Jasa Tenaga Kerja Bangunan Berbasis Android - As'ari, Abdul Haris; Suhendar, Agus (Journal of Information System Research (JOSH), 2024)
The purpose of this research is to develop a system that can assist the community, especially in the Pemalang region, in facilitating the management of construction workforce services and reducing unemployment in the surrounding areas. The specific focus of this study will be on the community in the Pemalang region. Currently, in Pemalang, the majority of the population still seeks construction labor services through manual methods, such as visiting service providers at their residences to offer jobs. Most people rely solely on personal connections. Consequently, if a service provider is already engaged in another project, customers may struggle to find an alternative. Meanwhile, there are many unemployed service providers outside the community seeking job opportunities. Additionally, some individuals feel that the wages for these workers are either insufficient or too high, necessitating negotiations for mutually agreed-upon compensation. The proposed construction workforce management system aims to create an application that assists the community in searching for services, negotiating terms, and estimating incurred expenses. For service searches, the system will enable users to search based on skills and location, allowing customers to find service providers according to the required expertise and in nearby areas to minimize transportation costs. Negotiations can be conducted remotely to determine prices and required departure times. Customers can also calculate costs to estimate their future expenditures. Service providers can upload their services for visibility, facilitating job acquisition and ultimately reducing unemployment.